Stretch to win - Frederick, Ann 1961-; Frederick, Chris 1958- (Champaign, IL Human Kinetics, 2017)
This proven program used by today's top athletes, coaches, trainers, and therapists will improve flexibility, reduce injury, and optimize performance. The new edition includes the latest research, new flexibility assessments, new stretching matrix, and dozens of the most effective stretches to personalize a program for any athlete, sport, or event
Chapter 1: Ten Principles for Optimal Flexibility; Chapter 2: Anatomy and Physiology of Flexibility; Chapter 3: Flexibility Training; Chapter 4: Flexibility for Sport Performance; Chapter 5: Flexibility Assessment; Chapter 6: Stretches for Fundamental Mobility; Chapter 7: Dynamic Stretches for Sports; Chapter 8: Assisted Stretching; Glossary; References; Index; About the Authors
Includes bibliographical references and index.
Keywords: Stretching exercises; Stretch (Physiology)